The Greek Neuropathic Pain Registry: The structure and objectives of the sole NPR in Greece. Issue 1 (16th July 2021) - Vadalouca, Athina; Alexopoulou‐Vrachnou, Evnomia; Rekatsina, Martina; Kouroukli, Irene; Anisoglou, Sousana; Kremastinou, Fani; Gabopoulou, Zoi; Chloropoulou, Panagiota; Micha, Georgia; Tsaroucha, Athanasia; Siafaka, Ioanna
Abstract: Objectives: Neuropathic pain (NP) is a complex condition that impairs the patients' quality of life. Registries are useful tools, increasingly used as they provide high‐quality data. This article aims to describe the Greek Neuropathic Pain Registry (Gr.NP.R.) design, the patients' baseline data, and real‐world treatment outcomes. Methods: The Gr.NP.R. collects electronically, stores, and shares real‐world clinical data from Pain and Palliative Care centers in Greece. It is a web‐based application, which ensures security, simplicity, and transparency. VAS, DN4, and Pain Detect were used for pain and NP assessment. Results: From 2016 to 2020, 5980 patients with chronic pain, of cancer or non‐cancer origin, were examined and 2334 fulfilled the NP inclusion criteria (VAS > 5, DN4 > 4, and Pain Detect ≥ 19). At the first visit, the mean age was 64.8 years, 65.5% were female patients, and 97.9% were Greek. The mean (SD) time from pain initiation to visiting the pain clinics was 1.5 (3.8) years. Most patients were undertreated. Following the patients' registration, the national guidelines were implemented. The majority of the prescribed medications were gabapentinoids (70.2%), especially pregabalin (62.6%), and opioids (tramadol, 55.3%). At visits 1 and 6, mean VAS was 7.1 and 5, and mean DN4 score was 5.6 and 3.5, respectively. Conclusions: The Gr.NP.R. provides information on the demographics, clinical progress, treatment history, treatment responses, and the drugs of choice for patients with cancer and non‐cancer NP. The collected data may help physicians plan the management of their patients.